Liquidity requirements, banks funding costs and profitability - Cascone, Emanuele (2019)
This dissertation follows an empirical approach to investigate the relationship between banks compliance with the liquidity coverage ratio (LCR) and their funding costs, profitability, and balance sheet composition. Moreover, the study looks at the relationship between bank-specific characteristics and the decision to maintain higher levels of LCR. For the scope of the analysis a panel dataset of 938 European banks over the period 2014-2018 is used. Consistent with expectations, the study shows that (i) smaller, less profitable and highly capitalized banks tend to present higher values for the LCR, (ii) banks with higher reported LCR show higher interest rates on retail deposits and interest on interest-bearing liabilities, (iii) the LCR does not influence the net interest margin of a bank, (iv) The LCR significantly negatively relates with the share of short-term deposits.